Green Corridors in Urban Landscapes, Case Study Nicosia Pedieos River - İnançoğlu, Selda; Özden, Özge; Kara, Can (European Journal of Sustainable Development, 2020)
Due to increasing population and expansion of cities, urban planning issues are becoming more important worldwide. It is realized that biological methodologies ought to be coordinated into urban arranging activities. Particularly in European cities, creating greenways and green corridors is a very recent phenomenon. The advancement of green space along urban waterways could moderate urban warmth island impacts, improve the physical and mental prosperity of city occupants, improve flood resilience and could also sustain biodiversity. The Pedieos River is the longest river in Cyprus. Like most of streams on the island, it is a non-enduring waterway, of fleeting nature that for the most part streams during the blustery winter months or after overwhelming precipitation occasions. A literature review was undertaken to discover the importance of rivers within the urbanized areas. It is known that the Pedieos River is firmly connected to the historical backdrop of Nicosia as it is one reason for the city's presence at the site. The increase of impermeable areas as a result of urbanization is also one of the main causes for flooding in recent years. In this research, the current situation of the river was investigated and its possible rehabilitation discussed for more sustainable city. The aim of this study is to recommend a feasible proposition by examining green territory zones and reason green passages along the Pedieos River so as to improve the living condition of Nicosia city. Keywords: Greenway, river, Pedieos River, urban planning